Disability inclusive disaster risk reduction with culturally and linguistically diverse (CALD) communities in the Hawkesbury-Nepean region: A co-production approach. (September 2021) - Crawford, Tonia; Villeneuve, Michelle; Yen, Ivy; Hinitt, Joanne; Millington, Micheal; Dignam, Madeleine; Gardiner, Elizabeth
Abstract: Fifteen percent of the global population live with some form of disability with refugees, migrants, indigenous peoples and prisoners with disabilities facing particular challenges accessing services. Despite this, people with disabilities are overlooked in disaster preparedness activities. In Australia, 29.7% of the population are born overseas and there is little understanding of how people with disabilities from culturally and linguistically diverse (CALD) communities are prepared and able to respond to disaster triggered by natural hazard (e.g. flood) and other emergencies. Disability Inclusive Disaster Risk Reduction (DIDRR) is an approach that directs attention to the support needs of people with disabilities, in interaction with their environment, to plan and prepare for emergencies. This project implemented a co-production approach building the capacity of our community partner to co-develop sustainable resources and build disaster preparedness awareness and action among people with disabilities from CALD communities in the flood-prone Hawkesbury-Nepean region in Australia. This paper reports on the outcomes of the workshops as well as reflection on the benefits, challenges and lessons learnt from the co-production approach that was used. Highlights: People with disabilities from CALD communities disproportionally affected by disasters. PCEP supports disability-inclusive disaster risk reduction in CALD communities. Co-produced workshops for CALD communities supports disaster planning.